Extracorporeal membrane oxygenation (ECMO): an option for cardiac reccovery from advanced cardiogenic shock - Ghodsizad, Ali; Singbartl, Kai; Körner, Matthias; Ruhparwar, Arjang (The heart surgery forum, 2017)
Mechanical circulatory support can prevent multi-organ failure and death in patients with advanced cardiogenic shock. Here we describe our experience using extracorporeal membrane oxygenation (ECMO) for treatment of advanced cardiogenic shock which has been used by our team for daily routine care in more than 200 patients during the last five years at the Penn State Medical Center.Venoarterial (VA) ECMO has been used as a viable therapeutic option for advanced cardiogenic shock as a bridge to recovery (BTR) or bridge to next decision (BTD). Our group performed a retrospective review of data from 155 patients from our single center cohort treated with VA ECMO for advanced cardiogenic shock. After successful ECMO treatment, the one year survival rate of patients with ischemic heart disease was 73.7 %, and the one year survival for patients with non-ischemic heart disease was 75%.
Gesehen am 08.06.2018